International Medullary Thyroid Carcinoma Grading System: A Validated Grading System for Medullary Thyroid Carcinoma. Issue 1 (1st January 2022) - Xu, Bin; Fuchs, Talia L.; Ahmadi, Sara; Alghamdi, Mohammed; Alzumaili, Bayan; Bani, Mohamed-Amine; Baudin, Eric; Chou, Angela; De Leo, Antonio; Fagin, James A.; Ganly, Ian; Glover, Anthony; et al.
Abstract : PURPOSE: Medullary thyroid carcinoma (MTC) is an aggressive neuroendocrine tumor (NET) arising from the calcitonin-producing C cells. Unlike other NETs, there is no widely accepted pathologic grading scheme. In 2020, two groups separately developed slightly different schemes (the Memorial Sloan Kettering Cancer Center and Sydney grade) on the basis of proliferative activity (mitotic index and/or Ki67 proliferative index) and tumor necrosis. Building on this work, we sought to unify and validate an internationally accepted grading scheme for MTC. PATIENTS AND METHODS: Tumor tissue from 327 patients with MTC from five centers across the United States, Europe, and Australia were reviewed for mitotic activity, Ki67 proliferative index, and necrosis using uniform criteria and blinded to other clinicopathologic features. After reviewing different cutoffs, a two-tiered consensus grading system was developed. High-grade MTCs were defined as tumors with at least one of the following features: mitotic index ≥ 5 per 2 mm 2, Ki67 proliferative index ≥ 5%, or tumor necrosis. RESULTS: Eighty-one (24.8%) MTCs were high-grade using this scheme. In multivariate analysis, these patients demonstrated decreased overall (hazard ratio [HR] = 11.490; 95% CI, 3.118 to 32.333; P < .001), disease-specific (HR = 8.491; 95% CI, 1.461 to 49.327; P = .017), distant metastasis-free (HR = 2.489; 95% CI, 1.178 to 5.261; P = .017), and locoregional recurrence-free (HR = 2.114; 95% CI, 1.065 to 4.193; P = .032) survivals. This prognostic power was maintained in subgroup analyses of cohorts from each of the five centers. CONCLUSION: This simple two-tiered international grading system is a powerful predictor of adverse outcomes in MTC. As it is based solely on morphologic assessment in conjunction with Ki67 immunohistochemistry, it brings the grading of MTCs in line with other NETs and can be readily applied in routine practice. We therefore recommend grading of MTCs on the basis of mitotic count, Ki67 proliferative index, and tumor necrosis. Abstract :